Introducing Software-Based Fault Handling Mechanism to Cope with Electromagnetic Interference (EMI) in Digital Electronic Circuits - Olayinka, Jinadu; Arobieke, Oluwole Olusegun; Idowu, Kayode; Samuel, Osafehiniti (Journal of Advanced Computer Science & Technology, 2012)
Digital circuits operating under radiation are subject to different kinds of permanent and transient effects. Most electromagnetic (EM) environment in which electronic systems have to operate is becoming increasingly hostile while dependence on electronics is widespread and increasing. The need for digital architectures to survive faults and remain dependable despite the multiple-fault injection nature of the electromagnetic interference (EMI) in microprocessors calls for the introduction of a software-based fault handling mechanism.Redundancy, which is a common answer to increasing error-coverage in most safety-critical applications offers higher dependability but for most low-cost computer based systems (including Digital Signal Processors), another technique is implemented for effectiveness. This paper implements the duplicate j-instruction rule on high-level programming to detect faulty jumps. Code redundancy and consistency checks covers the fault to increase system reliability